Food intake, Anemia Status, and Learning Achievement at Female Students in Gowa Regency, Indonesia - Nirwana, Nirwana; Ibrahim, Irviani Anwar; Syahrir, Sukfitrianty (Diversity: Disease Preventive of Research Integrity, 2021)
The main cause is due to food intake that lacks nutrients that can increase blood Hb levels. Anemia in school children can cause fatigue, lethargy, sleepiness, decreased concentration in learning which results in decreased learning achievement. This study aims to determine the description of food intake, anemia status, and learning achievement in young women of SMP Negeri 1 Parangloe, Gowa in 2019. This type of research is a descriptive study with a sample of 97 people. To find out the food intake of students, the 24-hour recall method was used, while the Cyanmethemoglobin method was used to measure Hb levels, and to measure their learning achievement was done by recording the average results of report cards. The results showed that 30.9% of female students suffered from anemia, 43.3% of female students with less energy intake, 28.9% with less protein intake, 44.3% with less iron intake, 58.8% with vitamin A intake is lacking, 56.7% with less vitamin C intake, 45.4% with less zinc intake. Regarding learning achievement, there are 23.7% of adolescent students with poor learning achievement. Seeing that there are still students with low academic achievement in SMP Negeri 1 Parangloe Gowa, it is recommended for students in addition to improving their learning, also increasing the consumption of foods rich in iron, protein, vitamin C, vitamin A, and zinc to prevent anemia which affects the learning achievement.